The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/pubmed/fdu065
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mortality and the burden of adult disease associated with adverse childhood experiences in England: a national survey

Abstract: BackgroundACE (adverse childhood experience) studies typically examine the links between childhood stressors and adult health harming behaviours. Using an enhanced ACE survey methodology, we examine impacts of ACEs on non-communicable diseases and incorporate a proxy measure of premature mortality in England.MethodsA nationally representative survey was undertaken (n = 3885, aged 18–69, April–July 2013). Socio-demographically controlled proportional hazards analyses examined the associations between the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
224
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(245 citation statements)
references
References 34 publications
(42 reference statements)
9
224
1
11
Order By: Relevance
“…In the current study, ACE score inversely correlated with diagnoses of hypertension, hypercholesterolemia, heart disease, skin cancer, and other cancers, despite previous reports linking these diseases in adulthood to adverse experiences early in life. 24,25,28,[32][33][34][35] There are a number of potential explanations for these findings. For example, participants ≥ 65 years of age were much less likely to report four or more ACEs and many of these conditions increase with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, ACE score inversely correlated with diagnoses of hypertension, hypercholesterolemia, heart disease, skin cancer, and other cancers, despite previous reports linking these diseases in adulthood to adverse experiences early in life. 24,25,28,[32][33][34][35] There are a number of potential explanations for these findings. For example, participants ≥ 65 years of age were much less likely to report four or more ACEs and many of these conditions increase with age.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of diagnosis and consequent lack of follow-up care for chronic diseases may contribute to the relationship between ACE score and premature death reported by several others. 22,25,32 Finally, it is worth considering the potential for resilience to adversity in the population, as described further below.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,6,1416,18,25,26 These results are also consistent with the literature in showing that ACEs have a dose–response effect in increasing exposure to risky behaviors and morbidity in adulthood. 2,4,15,18,3437 For instance, Felitti et al 2 showed a graded relationship between ACE scores and odds of behaviors/conditions, and Chartier and colleagues 34 found respondents who reported four or more adverse experiences in childhood had 172% increased odds of comorbid conditions, compared with those reporting zero. In addition, Gilbert et al 18 reported exposure to more ACEs was associated with greater odds of reporting fair/poor health, frequent mental distress, and disability.…”
Section: Discussionmentioning
confidence: 99%
“…After the exclusion of duplicate records and studies that did not match the inclusion criteria, 10 articles remained. After assessing the full text of these 10 studies, we excluded three articles [36][37][38] because they lacked the necessary data to be extracted. Finally, 7 studies [21][22][23][24][25][26][27] were included in this meta-analysis with one [26] identified from EMBASE and the rest from PubMed.…”
Section: 1mentioning
confidence: 99%